Subsidies for energy efficiency and alternative energy adoption programs: case study from Egypt taxi recycling program - Abdellatif, Omnia Ahmed M. (AUC Knowledge Fountain, 2011)
This thesis was developed to call in question the conventional perception that energy subsidies, especially in the service sector, are necessarily barriers to the adoption of improved technology. It provides a case study for an innovative program that supported energy efficiency and the adoption of alternative energy in the transportation sector and relied in part on subsidy savings. The program-Egypt's Taxi Recycling Program-was not only successful in reaching the targeted population effectively, but also lifted some of the fuel subsidies burden off the government budget. Cost Benefit Analysis (CBA) and Soft System Methodology (SSM) were applied to analyze the distribution of benefits from the Taxi Recycling program. The CBA was applied to define the main costs and benefits drawn by the two key stakeholders- the Egyptian Government and taxi owners participating in the program. The SSM was applied to have more detailed understanding of the role and the power of the stakeholders involved; in order to evaluate the performance of the stakeholders. The study findings indicated that the program has an overall positive impact on the different stakeholders involved. Since it was structured as a Public-Private-Partnership, the program offered significant opportunities to the private sector participating companies, either by stimulating vehicles sales and loan demands that would have not otherwise occurred, or by facilitating the communication channels among the different stakeholders involved. The program encountered some challenges that directly and indirectly affected the stakeholders involved. The taxi owners, however, had been the most influenced by the program's challenges. The challenges included: the advertising firm being unable to fulfill its commitments; the maintenance services and maintenance costs; the waiting periods for getting the new cars; the quality of the cars that were sold; and the adoption of natural gas as an alternative fuel. Nonetheless, the program had overall positive social impacts. Through applying CBA from the government perspective, we concluded that the benefits encountered from the program implementation far exceed the costs incurred by the government. Upon reaching the program target of changing around 40,000 old taxi vehicles operating in Greater Cairo Region, the program would save more than LE 380 million annually from the fuel subsidies assigned funds. As for the environmental impacts, the Taxi Recycling program has been divided into eleven separate projects called Certified Project Activities (CPAs); with an average of 4,576 recycled taxi vehicles per CPA. The preliminary assessment, based on CAPMAS's 2010 estimation of the costs associated with CO2 emissions' negative environmental impacts, showed that the new vehicles would result in annual average environmental benefits of 2.080 million US dollars per each Taxi-Recycling-CPA. In addition, these saved emissions represent potential government revenue if the government was able to sell the reduced emissions under the Clean Development Mechanism.